Efficacy and safety of high-dose esomeprazole and amoxicillin dual therapy versus bismuth-containing quadruple therapy for Helicobacter pylori infection: a multicenter, randomized controlled clinical trial. (December 2022) - Mei, Hao; Guo, Yan; Zhao, Jing-Tao; Yang, Jun; Sun, Wen-jing; Zhang, De-kui; He, Ping; Shi, Gang; Su, Na-yun; Han, Ran; Lan, Chun-Hui
Background: A high-dose proton pump inhibitor (PPI)-amoxicillin dual therapy has been investigated for treatment of patients with Helicobacter pylori ( H. pylori ) infection. Currently, the efficacy of this dual therapy remains inconclusive, with controversial findings from various single-center clinical trials. Objectives: To assess the efficacy and safety of high-dose dual therapy (HDDT) compared with the bismuth-containing quadruple therapy (BQT) in treatment-naive patients with H. pylori infection. Design: A multicenter, open-label, randomized controlled clinical trial. Methods: Three hundred and forty treatment-naïve patients with H. pylori infection were prospectively recruited from seven participating hospitals. The enrolled patients were randomized into one of two treatment groups: the HDDT group (esomeprazole, 20 mg four times daily; amoxicillin, 750 mg four times daily) and the BQT group (esomeprazole, 20 mg, twice daily; bismuth potassium citrate, 600 mg, twice daily; amoxicillin, 1 g, twice daily; metronidazole, 400 mg, four times daily). The primary outcome was eradication rate, and secondary outcomes were safety and patient compliance. Results: The eradication rates in the HDDT group versus the BQT group were 86.47% versus 87.06% on intention-to-treat (ITT) analysis, 91.88% versus 92.50% on modified ITT (MITT) analysis, and 91.77% versus 93.04% on per-protocol (PP) analysis, with no significant differences between the two groups. The patient compliance rates in the HDDT group versus the BQT group were 97.02% versus 95.86%, and no significant difference was found between the two groups. Notably, the HDDT group exhibited significantly lower incidence in the drug-induced adverse events (AEs) compared to the BQT group (16.67% versus 47.94%). Conclusion: HDDT is equally efficacious in eradicating H. pylori infection and resulted in good patient compliance and safety compared with BQT. These findings provide evidence in support of HDDT as a first-line treatment for H. pylori infection. Registration: This clinical trial was registered at The Chinese Clinical Trial Registry (trial registration number: ChiCTR2000039096).